Pseudalataspora vanderlingeni n. sp. (Myxosporea: Bivalvulida) from gall bladders of the Cape hakes Merluccius capensis Castelnau, and M. paradoxus Franca (Teleostei: Merlucciidae) - Reed, Cecile; Kalavati, Chaganti; Mackenzie, Ken; Collins, Catherine; Hemmingsen, Willy (Zootaxa, 2018)
A new species of myxosporean parasite is described from the gall bladders of the hakes Merluccius capensis Castelnau and M. paradoxus Franca (Pisces: Teleostei) caught off the west and south coasts of South Africa. The new species, Pseudalataspora vanderlingeni, is described morphologically and molecularly and compared with the 15 other species of Pseudalataspora previously described from marine fish. Although a molecular description is available on GenBank for only one of these 15 species, the morphological description supports the status of P. vanderlingeni as a new species. Earlier reports, without detailed descriptions, of Leptotheca sp. and Ceratomyxa sp. from the same hosts caught off Namibia were very likely to have been of P. vanderlingeni. These earlier studies reported high prevalences of infection, similar to those of >60% described in the present study. The effects of fixation and freezing on the dimensions of spores of Pseudalataspora spp. are described, and the status of the genus Pseudalataspora within the family Ceratomyxidae is discussed.